Parental risk factors for congenital diaphragmatic hernia - a large German case-control study - Felicitas Schulz; Ekkehart Jenetzky; Nadine Zwink; Charlotte Bendixen; Florian Kipfmueller; Neysan Rafat; Andreas Heydweiller; Lucas Wessel; Heiko Reutter; Andreas Mueller; Thomas Schaible (BMC, 2021)
Abstract Background Evidence for periconceptional or prenatal environmental risk factors for the development of congenital diaphragmatic hernia (CDH) is still scarce. Here, in a case-control study we investigated potential environmental risk factors in 199 CDH patients compared to 597 healthy control newborns. Methods The following data was collected: time of conception and birth, maternal BMI, parental risk factors such as smoking, alcohol or drug intake, use of hairspray, contact to animals and parental chronic diseases. CDH patients were born between 2001 and 2019, all healthy control newborns were born in 2011. Patients and control newborns were matched in the ratio of three to one. Results Presence of CDH was significantly associated with maternal periconceptional alcohol intake (odds ratio = 1.639, 95% confidence interval 1.101-2.440, p = 0.015) and maternal periconceptional use of hairspray (odds ratio = 2.072, 95% confidence interval 1.330-3.229, p = 0.001). Conclusion Our study suggests an association between CDH and periconceptional maternal alcohol intake and periconceptional maternal use of hairspray. Besides the identification of novel and confirmation of previously described parental risk factors, our study underlines the multifactorial background of isolated CDH.